CEREBROSPINAL FLUID ANALYSIS IN TUBERCULOUS MENINGITIS: DIAGNOSTIC, PROGNOSTIC, AND MONITORING PERSPECTIVES - Kiky Monica Soesanto; Ni Made Susilawathi; A.A. Raka Sudewi (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2026)
Tuberculous meningitis (TBM) is the most severe form of extrapulmonary tuberculosis, associated with high morbidity and mortality. This review aims to evaluate the role of cerebrospinal fluid (CSF) analysis in the diagnosis and prognosis, particularly in relation to mortality, as well as in therapeutic monitoring of TBM. A narrative literature review was conducted using studies published between 2010 and 2025 on CSF parameters in TBM. Studies reporting associations between CSF biomarkers and clinical outcomes were included. Eighteen eligible studies were analyzed qualitatively. CSF analysis plays a critical role in classifying TBM as definite, probable, or possible according to the Lancet criteria. Elevated CSF protein (≥2 g/L) and reduced glucose (<2.2 mmol/L) levels are strongly associated with mortality, reflecting severe inflammation and blood-brain barrier dysfunction. Additional markers such as CSF lactate, inflammatory cytokines, and CRP further support prognostication. Serial measurements of CSF parameters aid in monitoring treatment response, especially in cases with atypical clinical progress. This review also highlights the diagnostic and monitoring roles of CSF parameters throughout the course of TBM. CSF biomarkers, especially protein and glucose levels, are key to assessing disease severity, predicting outcomes, and guiding treatment strategies in TBM. These findings support the integration of CSF analysis into routine clinical algorithms for managing this life-threatening condition. Keywords: cerebrospinal fluid, diagnosis, monitoring, prognosis, tuberculous meningitis DOI: 10.35990/mk.v9n1.p104-114